Essays on natural disturbances and the provision of ecosystem services: monetizing impacts, assessing management tradeoffs, and measuring vulnerability - Elmer, Matthew Joseph, author; Kling, Robert W., advisor; Suter, Jordan F., advisor; Weiler, Stephan A., committee member; Loomis, John B., committee member (Colorado State University. Libraries, 2019)
This dissertation evaluates the effect of natural disturbances on the provision of ecosystem services. The first chapter examines whether small and frequent wildfires affect drinking water prices, finding both short-run and long-run effects on downstream surface water resources and subsequent prices. The results indicate that water system variable cost rises immediately following a wildfire, encouraging capital investment to reduce variable cost and resulting in a significant effect of wildfire on fixed cost in the long run. The second chapter examines how increased Forest Service spending on fire management has affected non-fire management. The results indicate that spending on fire has increased in western regions, with spending cuts across non-fire and fire programs, and large impacts on eastern regions. In many cases it is a combination of direct and indirect effects that contribute to spending cuts in non-fire programs, and many programs experience additional cuts not associated with fire. The third chapter explores climate-induced changes in rangeland grazing services on National Forest land in the Intermountain West, measuring vulnerability based on environmental, economic, and social factors. Grazing on National Forest land is found to contribute to local economic conditions but is also associated with adverse effects on rangeland vegetation and water when the forage appropriation rate is high. Overall, the drivers of vulnerability are heterogeneous across the region, suggesting that management decisions and adaptive efforts may be best served at the local level.
Keywords: environmental economics; monetize impacts; vulnerability; management tradeoffs; ecosystem services; natural disturbances